Suppression of meiotic crossovers in pericentromeric heterochromatin requires synaptonemal complex and meiotic recombination factors in Drosophila melanogaster. - Pazhayam, N.M.; Sagar, S.; Sekelsky, J. (Genetics, 2025)
The centromere effect (CE) is a meiotic phenomenon that ensures meiotic crossover suppression in pericentromeric regions. Despite being a critical safeguard against nondisjunction, the mechanisms behind the CE remain unknown. Previous studies found that different regions of the Drosophila pericentromere, encompassing proximal euchromatin, beta, and alpha heterochromatin, undergo varying levels of crossover suppression, raising the question of whether distinct mechanisms establish the CE in different regions. We asked whether different pericentromeric regions respond differently to mutations that impair features that may play a role in the CE. In flies with a mutation that affects the synaptonemal complex (SC), a structure that is hypothesized to have roles in recombination and crossover patterning, we observed a redistribution of pericentromeric crossovers from proximal euchromatin towards beta heterochromatin but not alpha heterochromatin, indicating a role for the SC in suppressing crossovers in beta heterochromatin. In flies mutant for mei-218 or rec, which encode components of a critical pro-crossover complex, there was a more extreme redistribution of pericentromeric crossovers towards both beta and alpha heterochromatin, suggesting an important role for these meiotic recombination factors in suppressing heterochromatic crossovers. We mapped crossovers in flies mutant for Su(var)3-9, which encodes histone H3-lysine-9 methyltransferase. Although we expected strong alleviation of crossover suppression in heterochromatin, no changes in pericentromeric crossover distribution were observed in this mutant, indicating that this vital heterochromatin factor is dispensable for preventing crossovers in heterochromatin. Thus, in Drosophila. melanogaster the meiotic machinery seems to play a more significant role in suppressing centromere-proximal crossovers than chromatin state.